Ivan Ohgienko Educational and Pedagogical Activity in Kamyanets-Podilsky State Ukrainian University: Historiographic Notes - Oleksandr Zavalnyuk (Pedagogical Discourse, 2013)
The contribution of the researchers to show the scientific and teaching activity of Ivan Ivanovych Ohienko, as the president and professor of the Ukrainian language history department in Kamyanets-Podilsky state Ukrainian university in 1919-1920, is analysed out in the article.